To Recognize the Causes of Stress and Its Effects Among Nurses Working in The Intensive Care Unit of Government Hospital Islamabad - Ullah, Naimat; Ali, Niaz; Naz, Aqeela; Khalid, Memoona; Khalid, Farzana; Shanala; Zainab, Ghulam (International Journal of Social Sciences and Management, 2022)
Introduction: Stress is an unwanted condition for any reason, affecting an individual’s life and developing socio-psychology problems. Identifying the main causes of the stress may vary different sources and especially for those who are working in a critical area of the hospital. Aim: The main focus of the study is to interpret the effects of stress and strategic methods for reducing the stress among Nurses, working in the Intensive care unit of PIMS hospital. Methodology: Cross-sectional study was conducted among ICU nurses of the PIMS hospital Islamabad. Our sample size was 150 nurses in critical areas, using a very simple method of obtaining the data. Result: Overall findings of the result are showing that ICU nurses have insufficient knowledge about operating the main machinery creating more stress, conflicts with co- workers and doctors, prolonged shifts, and lack of support from seniors. These are the main reasons for the stress. The data was collected by the distribution of an official format questionnaire among the ICU nurses and their data was kept confidential. Conclusion: The main motive of the study is to evaluate the knowledge of stress coping skills among ICU nurses and managerial skills and techniques which can reduce stress levels. Cognitive therapies and different training programs should be arranged by the ICU management and spare some time for recreational activities, maintain a balanced diet and keep busy with patient care and avoid unnecessary activities. Seniors and doctors should encourage their juniors and create a pleasant, positive atmosphere. All these activities can promote the health status of the patient. Int. J. Soc. Sc. Manage. Vol. 9, Issue-3: 94-102.